Oracle 11g PL/SQL programming - Casteel, Joan (Course Technology, Cengage Learning, 2013)
Helps you learn how you use PL/SQL programming language with software programs in large companies today: Oracle[registered]11g. This title provides an overview of the PL/SQL programming language from a developer's perspective. It begins with a introduction to fundamental PL/SQL concepts before progressing to writing and testing PL/SQL code.